A 25.1% Efficient Stand‐Alone Solar Chloralkali Generator Employing a Microtracking Solar Concentrator. Issue 9 (29th November 2017) - Chinello, Enrico; Modestino, Miguel A.; Coulot, Laurent; Ackermann, Mathieu; Gerlich, Florian; Psaltis, Demetri; Moser, Christophe
Abstract: Chlorine is a large‐scale chemical commodity produced via the chloralkali process, which involves the electrolysis of brine in a membrane‐based electrochemical reactor. The reaction is normally driven by grid electricity; nevertheless, the required combination of voltage–current can be guaranteed using renewable power (i.e., photovoltaic electricity). This study demonstrates an off‐grid solar‐powered chlorine generator that couples a novel planar solar concentrator, multijunction InGaP/GaAs/InGaAsNSb solar cells and an electrochemical cell fabricated via additive manufacturing. The planar solar concentrator consists of an array of seven custom injection‐molded lenses and uses microtracking to maintain a ± 40° wide angular acceptance. Triple‐junction solar cells provide the necessary potential (open‐circuit voltage, V OC = 3.16 V) to drive the electrochemical reactions taking place at a De Nora DSA insoluble anode and a nickel cathode. This chloralkali generator is tested under real atmospheric conditions and operated at a record 25.1% solar‐to‐chemical conversion efficiency (SCE). The device represents the proof‐of‐principle of a new generation stand‐alone chlorine production system for off‐grid utilization in remote and inaccessible locations. Abstract : Chlorine is a chemical of vast utilization, currently generated via electrochemical routes, which accounts for a great amount of energy consumption. Powering the process with multijunction photovoltaics (coupled with an innovative planar solar concentrator) has proven to result in ultrahighly efficient operation. This approach paves the way toward chlorine industry decarbonization and a practical off‐grid solar‐chlorine generator, which can sanitize water in remote locations.